Technology adoption under costly information processing - Dominik Naeher (International Economic Review, 2021)
A new explanation for imperfect technology adoption is proposed. In the model, agents allocate scarce attention rationally between actions and decide whether and how to adopt a technology. Introducing constraints to information processing gives rise to attentional barriers to technology adoption, which affect optimal adoption behavior. The model can explain why individuals (i) fail to adopt profitable technologies, (ii) fail to make the best use of adopted technology, (iii) treat complementary technologies as substitutes, and (iv) change their adoption decision back and forth over time. The model complements existing learning models and is consistent with empirical~evidence.
Keywords: 330